2005
DOI: 10.1160/th04-12-0799
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between factor XIII activity, fibrinogen, haemostasis screening tests and postoperative bleeding in cardiopulmonary bypass surgery

Abstract: We investigated the relationship between factor XIII, fibrinogen, blood coagulation screening tests and postoperative bleeding in 98 patients undergoing cardiopulmonary bypass (CPB) surgery. All patients received aprotinin. Blood samples were collected preoperatively (T1),after termination of CPB (T2),12 h (T3) and 24 h (T4) after surgery to determine FXIII activity, fibrinogen, platelet count, prothrombin time (PT), activated partial thromboplastin time (APTT) and D-dimers (DD). Laboratory results were correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 20 publications
(34 reference statements)
9
133
0
2
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34] Some have found a positive correlation between APTT and postoperative hemorrhage following cardiac surgery. 26,28,30,[35][36][37][38][39] Very few studies, in fact, have specified their transfusion algorithms for the management of hemorrhage, [26][27][28]40 thus making it difficult to ascertain how elevated APTT was interpreted and dealt with in most studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31][32][33][34] Some have found a positive correlation between APTT and postoperative hemorrhage following cardiac surgery. 26,28,30,[35][36][37][38][39] Very few studies, in fact, have specified their transfusion algorithms for the management of hemorrhage, [26][27][28]40 thus making it difficult to ascertain how elevated APTT was interpreted and dealt with in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of coagulation factors has been well described in cardiac surgery, 30,46,47 as has the dilution of factors resulting from red cell transfusion and volume expanders. In addition, altered blood flow during CPB might have resulted in decreased synthetic function of coagulation factors by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The pathophysiology of post bypass bleeding, particularly in complex cardiac surgery, is incompletely understood, but appears to be multifactorial, with platelet dysfunction and decreased fibrinogen concentrations playing important roles. [15][16][17] Australian transfusion guidelines 14 suggest that cryoprecipitate may be indicated when bleeding is associated with decreased fibrinogen, and that fresh frozen plasma may be indicated for bleeding after cardiac surgery. Our guideline recommends platelet and cryoprecipitate transfusion in response to decreases in platelets and fibrinogen concentrations in lieu of using fresh frozen plasma alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is converted in plasma by thrombin into a fibrin clot at the site of tissue damage in order to minimize blood loss and initiate tissue repair [9]. Administration of prophylactic fibrinogen has been shown to reduce postoperative bleeding after coronary artery bypass graft (CABG) [10] and previous studies have reported an inverse correlation between preoperative concentration of fibrinogen in plasma and the volume of postoperative bleeding after CABG [11][12][13][14][15]. This indicates that preoperative fibrinogen plasma concentration, even within the normal range, is a limiting factor for haemostasis after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%